Estimating building energy ratings for the residential building stock: Location and occupancy - John Curtis; Niamh Devitt; Adele Whelan (The Economic and Social Research Institute (ESRI), 2014)
The common EU framework for assessing the energy performance of residential buildings and awarding Energy Performance Certificates (EPCs) is an important resource in the context of informing effective policy measures to improve energy efficiency. However, properties that have been assessed to-date are not likely to be fully representative of the entire housing stock and therefore provide a faulty baseline from which to devise policy actions. The paper presents a methodology to estimate the energy performan ce of all residential properties and , combined with census data , identifies what distinguishes the most energy inefficient properties, whether it is location, ownership, age or other characteristic. Data from the Irish EPC database suggest that 25% of the Irish residential housing stock is in the most energy inefficient categories, whereas the methodology developed here suggests that it is substantially higher at 35%. The results also indicate that there is a substantially greater likelihood that the elderly, or families living in rental properties live in the most energy inefficient properties.
Keywords: 330